Efforts to Increase Activities and Learning Outcomes During the Covid-19 Pandemic at SD Muhamadiyah 1 Waru - Esti Budi Mu’afiqoh (International Consortium of Education and Culture Research Studies, 2021)
Education is the learning of knowledge, skills, and habits of a group of people that are passed down from one generation to the next through teaching, training, or research. Education often takes place under the guidance of others, but it is also possible to be self-taught. The Covid-19 pandemic has disrupted the conventional learning process. The government's recommendation is to do online learning. Online learning is one alternative that can solve these problems in order to break the chain of virus spread. The purpose of the research is how an agency seeks to increase activity and learning outcomes during the covid-19 pandemic. The research method used in this study is descriptive qualitative with data collection methods through observation to an agency, by digging data through sources who are willing to provide information related to the articles made. The results showed that the teacher chose the right learning method and the school supported it by facilitating the use of existing media as a means of delivering distance learning material and conducting periodic learning evaluations. The positive contribution in this study is intended to provide information to the management of educational institutions that learning activities during the Covid-19 period can be improved by fulfilling distance learning facilities and selecting appropriate learning methods and presenting materials